2021
DOI: 10.1002/pbc.29174
|View full text |Cite
|
Sign up to set email alerts
|

Parental limited English proficiency in pediatric stem cell transplantation: Clinical impact and health care utilization

Abstract: Background: Limited English proficiency (LEP) is associated with adverse clinical outcomes. The clinical impact of LEP in hematopoietic stem cell transplant (HSCT) has not been studied. The objectives of this study were to compare HSCT outcomes and health care utilization of Hispanic pediatric patients with and without parental LEP. Methods:We conducted a retrospective review of Hispanic/Latino pediatric patients receiving HSCT at a single institution. Families were identified as LEP or English proficient (EP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Use of a qualified healthcare interpreter promotes justice in information shared and protected. Inequities in pain management, 11 adverse events, 12 hospitalization duration, 13,14 and return visits to the emergency department 15 have affected patients with NELP. With respect to beneficence, professional healthcare interpreter use is associated with improved clinical outcomes, discharge education processes, patient comprehension, and patient satisfaction for those with NELP 4,5,16 .…”
Section: Patient Right To Language Services: Ethical Principlesmentioning
confidence: 99%
“…Use of a qualified healthcare interpreter promotes justice in information shared and protected. Inequities in pain management, 11 adverse events, 12 hospitalization duration, 13,14 and return visits to the emergency department 15 have affected patients with NELP. With respect to beneficence, professional healthcare interpreter use is associated with improved clinical outcomes, discharge education processes, patient comprehension, and patient satisfaction for those with NELP 4,5,16 .…”
Section: Patient Right To Language Services: Ethical Principlesmentioning
confidence: 99%
“…Having LEP is associated with reduced survival in pancreatic cancer 8 and higher risk of treatment failure in head and neck cancers 9 . There are no published studies on LEP and acute leukaemia mortality, but a US study of Hispanic families in a paediatric stem cell transplant setting showed that parental LEP was significantly associated with prolonged hospitalisation 10 …”
Section: Figurementioning
confidence: 99%
“… 9 There are no published studies on LEP and acute leukaemia mortality, but a US study of Hispanic families in a paediatric stem cell transplant setting showed that parental LEP was significantly associated with prolonged hospitalisation. 10 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An especially important suggestion that McKee et al (7) discuss is the need for improved language services for patients and families with Limited English Proficiency (LEP), correctly citing that patients of any race or ethnicity with LEP are known to have poor health outcomes and poor access to healthcare services. Specific to pediatric HSCT, parental LEP is directly associated with prolonged hospitalization and cytomegalovirus reactivity, and indirectly associated with posttransplant complications and death (13). As reported in their limitations, the database records used for this study were limited to standard diagnosis and consultation queries (7).…”
mentioning
confidence: 99%